2012
DOI: 10.3928/00989134-20110706-01
|View full text |Cite
|
Sign up to set email alerts
|

Delirium Superimposed on Dementia: Accuracy of Nurse Documentation

Abstract: Delirium is an acute, fluctuating confusional state that results in poor outcomes for older adults. Dementia causes a more convoluted course when coexisting with delirium. This study examined 128 days of documentation to describe what nurses document when caring for patients with dementia who experience delirium. Nurses did not document that they recognized delirium. Common descriptive terms included words and phrases indicating fluctuating mental status, lethargy, confusion, negative behavior, delusions, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 46 publications
1
39
1
Order By: Relevance
“…These trigger words have been used in a previously validated chart-based approach to identifying delirium 7 and were similar to those used in previous studies that extracted key words for confusion from electronic records. 14, 15 Examples of trigger words were: ‘mental status change’, ‘disoriented/re-oriented’, ‘unresponsive’, and ‘agitated’. Table 3 includes a full listing of trigger words.…”
Section: Methodsmentioning
confidence: 99%
“…These trigger words have been used in a previously validated chart-based approach to identifying delirium 7 and were similar to those used in previous studies that extracted key words for confusion from electronic records. 14, 15 Examples of trigger words were: ‘mental status change’, ‘disoriented/re-oriented’, ‘unresponsive’, and ‘agitated’. Table 3 includes a full listing of trigger words.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, nurses typically do not receive formal training in standardized cognitive or delirium assessment. 3,11,1416 …”
Section: Introductionmentioning
confidence: 99%
“…The mental status examination is a structured evaluation of physical (i.e., appearance, behavior, motor activity), emotional (i.e., attitude, mood/affect, thoughts, perceptions and judgment), and cognitive (i.e., orientation, attention, level of consciousness, speech, memory, abstraction) domains that describe a person’s state of mind (Trzepacz & Baker, 1993). Nurses are familiar with certain aspects of the mental status examination (i.e., orientation, level of consciousness) but pay less attention to other critical components (Steis & Fick, 2012). Attention is one such component.…”
Section: Overview Of Attentionmentioning
confidence: 99%
“…Studies have shown that although nurses and physicians prefer and are most comfortable with using orientation as an indicator of change in mental status, in fact, it is one of the least useful indicators (Inouye, Foreman, Mion, Katz, & Cooney, 2001; Steis & Fick, 2012). For this reason and others, nurses must begin to shift their thinking to make assessment of attention a priority over other constructs of mental status.…”
Section: Difficulties Assessing Attentionmentioning
confidence: 99%
See 1 more Smart Citation